Gestión administrativa y su incidencia en el control de operaciones de la empresa Super Tia cantón Quevedo, año 2023 - Montoya Torres, Darwin Antonio (2025)
The proposal of this work is the elaboration of the Administrative Management that allows to have a better operational control in the company Almacenes Tía to make each of the business activities more efficient, because in the current environment it is a fact that only those companies that base their administration on strategic planning and that anticipate possible market changes succeed. Almaneces Tía is a chain of stores that offers quality, variety and economy products in different categories. You can buy online or pick up in store cell phones, TVs, refrigerators, stoves, laptops and more1. In addition, Tía has more than 450 points of sale in several countries, including supermarkets, hypermarkets, shopping malls, discount stores and online stores.